Legal and Human Rights Review of The Implementation Of Prenuptial Agreements Based On The Principles Of Propriety, Fairness and Good Faith - Nursyamsiah, Ayu; Daming, Saharuddin; Ratnawaty, Latifah (JURNAL MAHASISWA YUSTISI, 2023)
Prenuptial agreement one of the legal tools that can be used to defend the rights of husband and wife, they have opportunity to be open to each other, express opinions, agreed wishes and do not harm. Article 1338 of the Indonesian Civil Code and Article 1339 of the Indonesian Civil Code, are absolute in accordance with the principles of propriety, justice and good faith. Problem statement: stakeholders' views on the implementation of prenuptial agreements based on propriety, justice, good faith and human rights, and the principles of propriety, fairness and good faith can be applied in prenuptial agreements and their application in accordance with human rights standards. Type of research: empirical normative. Result: the implementation of the prenuptial agreement is carried out with due regard to propriety, fairness and good faith of the parties, it is not allowed to reduce and violate the rights of the other party, if that happens it can be submitted for cancellation to the court. The application of principles in accordance with human rights is by having equal opportunities to express needs in the prenuptial agreement properly, providing protection and justice to the couple, having good intentions respecting each other in good faith.